Optimasi Dosis Biokoagulan Biji Pepaya (Carica papaya L.) dalam Penurunan Parameter TSS, BOD, dan COD pada Limbah Tahu - Yasmine, Yovansyach Arraficha; Afrianisa, Rodu Dhuha (Environmental Engineering Journal ITATS, 2025)
The wastewater produced by tofu industries contains high concentrations of organic substances such as proteins, carbohydrates, and fats, which can significantly increase the Biological Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) if not properly treated. Therefore, treatment is required before the water can be discharged into receiving water bodies. This study was conducted using the coagulation–flocculation method, with papaya seed powder used as a natural coagulant. The objective of the research was to determine the optimum dosage of papaya seed bio-coagulant and to evaluate its effectiveness in reducing TSS, BOD, and COD levels under different slow mixing speeds. The dosage variations used in this study were 0.2 g/L, 0.4 g/L, 0.6 g/L, 0.8 g/L, and 1 g/L. The rapid mixing was carried out at 150 rpm for 1 minute, followed by slow mixing at 40 rpm and 30 rpm for 15 minutes, and then sedimentation for 30 minutes. The results showed that the optimum dosage of papaya seed bio-coagulant was 0.4 g/L when using rapid mixing at 150 rpm combined with slow mixing at 40 rpm or 30 rpm. At 150/40 rpm mixing speed, the percentage reductions in TSS, BOD, and COD were 41.15%, 55.94%, and 46.60% respectively. Meanwhile, at 150/30 rpm mixing speed, the reductions were 65%, 61.78%, and 51.78% respectively.